2016
DOI: 10.4236/ojst.2016.66021
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Role of Palatal Tonsil Hypertrophy in Sleep Apnea Patients: Cephalometric Analysis

Abstract: The purpose of this research was to elucidate the relationship between tonsillar hypertrophy and Obstructive Sleep Apnea Syndrome (OSAS) in terms of cephalometric analysis, as well as to determine factors that affect OSAS severity. 25 patients were enrolled in this study. Lateral cephalograms of the subjects were taken. Disease severity was evaluated by the Apnea Hypopnea Index (AHI). Cephalometric measurements (angle between line S-N and line N-A (SNA), angle between line S-N and line N-B (SNB), distance betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…The 46 analyses of 23 cases demonstrated that V2 and CSA2 were related to SNB, consistent with the results of our OSA study 12 . The SNB is patient‐specific data indicating the current position of the mandible relative to the skull and can be measured before and after surgery.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The 46 analyses of 23 cases demonstrated that V2 and CSA2 were related to SNB, consistent with the results of our OSA study 12 . The SNB is patient‐specific data indicating the current position of the mandible relative to the skull and can be measured before and after surgery.…”
Section: Discussionsupporting
confidence: 85%
“…Kita et al 5 and Yajima et al 6 were related to SNB, consistent with the results of our OSA study. 12 The SNB is patient-specific data indicating the current position of CFD is an analysis derived from CT that can analyse dynamic functions. In the future, it will be possible to predict postoperative…”
Section: Discussionmentioning
confidence: 99%
“…Cephalometry records the following variables: SNA, sella to nasion foe sagittal positioning of the maxillary; SNB, sella to nasion for the sagittal positioning of the mandible; PAS, posterior airway space; MPH, mandibular plane to hyoid bone [47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…In these diseases, it is important to find an anatomic stenosis site for diagnosis and treatment. As search methods for stenosis, analysis by macroscopic observation, endoscopic observation, cephalometric analysis [2][3][4][5][6][7], CT [8], and MRI [9] have been reported. However, these tests are for observing the resting state, and do not show the actual function and the airflow.…”
Section: Introdcutionmentioning
confidence: 99%